Straight & narrow? : compassion & clarity in the homosexuality debate - Schmidt, Thomas E. (Downers Grove, Ill. : InterVarsity Press, 1995)
Too often, Thomas Schmidt writes, the charged battle over homosexuality generates slogans and accusations--obscuring the struggling persons at the center of the argument.
In this book Schmidt brings the discussion back into empathetic contact with the circumstances and the choices of individuals. At the same time he offers thoroughly researched and up-to-date information and assessment from an evangelical Christian perspective on all the main points of the debate. He includes chapters on what the Bible really says (and means) about homosexuality, the health effects of homosexual behavior, whether or not people are born with homosexual orientations, and the cogency of recent progay reconstructions of history such as John Boswell's.
About me, about you -- What all the fuss is about -- Sexuality from the beginning -- Romans 1:26-27 : the main text in context -- From Sodom to Sodom -- The price of love -- The great nature-nurture debate -- Straight & narrow? -- Postscript : a letter to a friend.
Includes bibliographical references (pages 219-236 and indexes.
Keywords: Homosexuality -- Religious aspects -- Christianity; Homosexuality -- Moral and ethical aspects; Evangelicalism